From Recollections to Current Impressions - Victoria Astrakhantseva; Inna Druzhinina (Проект Байкал, 2019)
The article analyzes 58 issues of Project Baikal journal. It provides a historical excurse to the foundation of the journal and tells about certain sections and authors. It features the level of graphic materials and transformation of printed editions. The analysis reveals the scientific value of the materials contributed by famous authors. The article points out a growing interest among architects and other specialists in submitting scientific and research papers.